2022
DOI: 10.3390/pr10061148
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Primary Breakup of Disturbed Liquid Jet Sprays Using a VOF Model and LES Method

Abstract: In this study, the primary breakup of a high-speed diesel jet is investigated using a CFD methodology that combines an LES model with a VOF technique for free surface capture. Inner-nozzle turbulence and cavitation are simplified as the sinusoidal radial velocity with a given amplitude and frequency. The ligament and droplet formation process are captured, the liquid jet is disturbed by the radial velocity, and umbrella-shaped crests are created. Meanwhile, ligaments are formed from the edges of crests because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…It is important to remember that liquid fuel disintegrates into ligaments and large droplets at the stage of internal flow, before the spray comes out of the nozzle. This process, known as primary break-up, is caused by the internal flow cavitation and turbulence instability [45][46][47]. Figure 3 is break-up regimes of droplet.…”
Section: Spray Atomizationmentioning
confidence: 99%
“…It is important to remember that liquid fuel disintegrates into ligaments and large droplets at the stage of internal flow, before the spray comes out of the nozzle. This process, known as primary break-up, is caused by the internal flow cavitation and turbulence instability [45][46][47]. Figure 3 is break-up regimes of droplet.…”
Section: Spray Atomizationmentioning
confidence: 99%
“…With sufficient computational resources, more information on turbulence can be obtained. The method has been extensively used to study nozzle cavitation [20][21][22][23]. Kim et al [24] used LES to investigate the influences of initial momentum thickness on free jet flow in a circular hole, discovering that these factors have a significant impact on the free jet's flow characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The LES-VOF model provides an excellent simulation strategy for studying the effects of dynamic processes, such as the deformation, attraction, repulsion [20,21], and breakup [22,23] of discrete particles. Liu et al used the LES-VOF model to investigate the primary breakup of a high-speed diesel jet, and the ligament and droplet formation processes were effectively captured and the effects of the surface wave characteristics and the liquid structure were revealed [24]. Saeedipour et al suggested that the LES-VOF model effectively predicted local turbulence characteristics as well as the energy spectra and accurately calculated industrial problems of dispersed droplets under a coarse grid in heterogeneous flow with density contrasts [25].…”
Section: Introductionmentioning
confidence: 99%